A novel multi-magnetometer facility for on-ground characterization of spacecraft equipment. (November 2019) - Tsatalas, S.; Vergos, D.; Spantideas, S.T.; Kapsalis, N.C.; Kakarakis, S.-D.J.; Livanos, N.A.; Hammal, S.; Alifragkis, E.; Bougas, A.; Capsalis, C.N.; Junge, A.
Highlights: Multi Magnetometer Facility aims at magnetic characterization of space equipment. The facility performs a snap-shot measurement of the magnetic signature of a unit. Fast measurement procedure and modeling software result in more reliable results. The operation of the facility is validated with measurements of well-known sources. Abstract: This paper aims to provide the research and development activities of ESA contract 4000111736/14/NL/GLC on Multi-Magnetometer Methods for Magnetic Dipole Modelling awarded to a consortium, consisting of EMTECH SPACE P.C. and National Technical University of Athens. In the frame of this activity, the rotational magnetic measurements of a unit under test are replaced by an increasing number of fixed magnetic field sensors, intended to perform a snap-shot measurement of its DC magnetic field. The scope of the research is to identify the most efficient number of magnetometers and their spatial geometry in order to effectively characterize magnetic sources consisting of several dipoles and quadrupoles. At later stages of the activity, the construction of a novel Multi-Magnetometer Facility was realized. The mechanical design of the facility is extensively illustrated and its capability to characterize magnetic field signatures is validated with a set of a-priori known magnetic sources.